1989
DOI: 10.1017/s0031182000061023
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofTrypanosoma congolenseandTrypanosoma bruceisubspecies by DNA amplification using the polymerase chain reaction

Abstract: The nuclear DNA of Trypanosoma congolense contains a family of highly conserved 369 base pair (bp) repeats. The sequences of three cloned copies of these repeats were determined. An unrelated family of 177 bp repeats has previously been shown to occur in the nuclear DNA of Trypanosoma brucei brucei (Sloof et al. 1983a). Oligonucleotides were synthesized which prime the specific amplification of each of these repetitive DNAs by the polymerase chain reaction (PCR). Amplification of 10% of the DNA in a single par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
252
0
9

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(264 citation statements)
references
References 31 publications
3
252
0
9
Order By: Relevance
“…The supernatant containing the DNA was stored at -20°C or used directly for PCR. A first amplification protocol to detect Trypanosoma brucei s.l., was proceeded on the extracts of all the samples using the primers TBR1 (5'-GAATATTAAA CAATGCGCAG-3')/TBR2 (5'-CCATTTATTAGCTTTGTT GC-3') (Moser et al, 1989). This was followed by a second amplification on T. brucei s.l.…”
Section: Extraction and Amplification Of Dnamentioning
confidence: 99%
“…The supernatant containing the DNA was stored at -20°C or used directly for PCR. A first amplification protocol to detect Trypanosoma brucei s.l., was proceeded on the extracts of all the samples using the primers TBR1 (5'-GAATATTAAA CAATGCGCAG-3')/TBR2 (5'-CCATTTATTAGCTTTGTT GC-3') (Moser et al, 1989). This was followed by a second amplification on T. brucei s.l.…”
Section: Extraction and Amplification Of Dnamentioning
confidence: 99%
“…In an effort to develop more sensitive assays, PCR technology has been introduced to specifically detect T. cruzi DNA in blood samples from chagasic patients, opening new possibilities in the diagnosis and follow-up assessment of chemotherapy (Moser et al 1989, Sturm et al 1989, Avila et al 1991, Britto et al 1993, 1995, Wincker et al 1994a, b, Junqueira et al 1996, Gomes et al 1998, Galvão et al 2003. Reconstitution experiments showed that PCR procedures are able to detect the equivalent of a single parasite cell in 10-20 mL of whole blood (Moser et al 1989, Avila et al 1991, Britto et al 1993.…”
Section: Usefulness Of Pcr For Establishing Drug Efficacymentioning
confidence: 99%
“…Reconstitution experiments showed that PCR procedures are able to detect the equivalent of a single parasite cell in 10-20 mL of whole blood (Moser et al 1989, Avila et al 1991, Britto et al 1993. However, there are large genetic differences between distinct T. cruzi strains related to their biological variability, such as virulence or variable susceptibility to the immune response (control of parasitaemia) developed after the acute phase of human infection.…”
Section: Usefulness Of Pcr For Establishing Drug Efficacymentioning
confidence: 99%
“…17 We have found that the PCR, when used with the T. cruzi-specific primers TCZ-1 and TCZ-2, which anneal to a highly repetitive sequence of T. cruzi nuclear DNA, 18 is far more sensitive than direct microscopic observation for the neonatal diagnosis of T. cruzi infection. 19 In this study, we used the PCR to detect T. cruzi infection in blood samples of newborns for early diagnosis and to monitor treatment.…”
mentioning
confidence: 99%